2021
DOI: 10.9734/irjpac/2021/v22i230384
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Climate Change and the Recent Development of an Artificial Tropical Estuary on the Mobility and Distribution of Phosphorus: Case of Vridi Channel (Côte d'Ivoire)

Abstract: This study focused on the effects of the climate change and the recent modification of Vridi channel on the mobility and distribution of phosphorus (P) in its superficial sediments. To best estimate this fact, the annual mobility and distribution of P were followed and compared before and after this development during two different annual periods, marked differently by the climate change effects. The first annual period has covered the period from April 2014 to March 2015 and this channel presented its former … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(119 reference statements)
0
1
1
Order By: Relevance
“…[24] that ranged from 35-66%. The lower values obtained in this study might be due to rock formation as well as difference in geological locations [26].…”
Section: Results and Discussion 1) Phosphorus Speciationcontrasting
confidence: 59%
See 1 more Smart Citation
“…[24] that ranged from 35-66%. The lower values obtained in this study might be due to rock formation as well as difference in geological locations [26].…”
Section: Results and Discussion 1) Phosphorus Speciationcontrasting
confidence: 59%
“…Its mean concentration for all samples was 15.88±9.21 µg P g -1 , whereas Maslukah et al [10] reported this fraction as the most abundant in a similar study. Since this fraction is generally derived from residual bones and teeth of dead marine organisms, it was low in this study probably due to the composition of the deposit and the type of rock formation in the area [26]. Average concentration of detrital apatite P for all points was 38.28±12.78 µg P g -1 and it ranged from 12.32±0.73 µg P g -1 to 57.59±3.00 µg P g -1 (Figure 3d).…”
Section: Results and Discussion 1) Phosphorus Speciationmentioning
confidence: 86%